Electronic states of pseudospin-1 fermions in dice lattice ribbon - Oriekhov, D.O.; Gorbar, E.V.; Gusynin, V.P. (Физика низких температур, 2018)
Boundary conditions for the two-dimensional fermions in ribbons of the hexagonal lattice are studied in the
dice model whose energy spectrum in infinite system consists of three bands with one completely flat band of
zero energy. Like in graphene the regular lattice terminations are of the armchair and zigzag types. However,
there are four possible zigzag edge terminations in contrast to graphene where only one type of zigzag termination is possible. Determining the boundary conditions for these lattice terminations, the energy spectra of
pseudospin-1 fermions in dice model ribbons with zigzag and armchair boundary conditions are found. It is
shown that the energy levels for armchair ribbons display the same features as in graphene except the zero energy flat band inherent to the dice model. In addition, unlike graphene, there are no propagating edge states localized at zigzag boundary and there are specific zigzag terminations which give rise to bulk modes of a metallic
type in dice model ribbons. We find that the existence of the flat zero-energy band in the dice model is very robust and is not affected by the zigzag and armchair boundaries. Вивчено граничні умови для двовимірних ферміонів на
стрічці гексагональної гратки в дайс-моделі, енергетичний
спектр якої в нескінченній системі складається з трьох зон,
одна з яких є повністю плоскою зоною із нульовою енергією.
Подібно графену регулярними краями стрічки є два типи
границь у вигляді крісла та зигзагу. Існують чотири можливих границі типу зигзаг на відміну від графену, де тільки
один тип таких границь можливий. Знайдено енергетичний
спектр ферміонів із псевдоспіном одиниця в дайс-моделі з
граничними умовами у вигляді крісла та зигзагу. Показано,
що енергетичні рівні для стрічок з граничними умовами у
вигляді крісла аналогічні рівням в графені, включаючи додатково плоску зону нульової енергії. З іншого боку, на
відміну від графену, не існує крайових мод, локалізованих на
границях стрічки, проте існують зигзаг границі, для яких
моди металічного типу присутні усередині стрічки. Енергетична дисперсія повністю плоскої енергетичної зони дайсмоделі не змінюється в присутності граничних умов обох
типів, які інваріантні відносно симетрій зарядового сполучення та обернення часу Исследованы граничные условия для двумерных фермионов на полоске гексагональной решетки в дайс-модели, энергетический спектр которой в бесконечной системе состоит из
трех зон, одна из которых является полностью плоской зоной с
нулевой энергией. Подобно графену регулярными краями
полоски являются два типа границ в виде кресла и зигзага.
Существуют четыре возможных границы типа зигзаг в отличие от случая графена, где только один тип таких границ возможен. Найден энергетический спектр фермионов с псевдоспином единица в дайс-модели с граничными условиями в
виде кресла и зигзага. Показано, что энергетические уровни
для полосок с граничными условиями в виде кресла аналогичны уровням в графене, включая дополнительно плоскую зону
нулевой энергии. С другой стороны, в отличие от графена, не
существует краевых мод, локализованных на границах полоски, однако имеются зигзаг границы, для которых существуют
моды металлического типа внутри полоски. Энергетическая
дисперсия полностью плоской энергетической зоны дайсмодели не изменяется в присутствии граничных условий обоих типов, которые инвариантны относительно симметрий зарядового сопряжения и обращения времени.